Geotechnical properties of well-compacted coal wash reject for use as backfill in rehabilitation projects, literature review and testing for assessment of settlement characteristics - Du, S.; Ghimire, S.; Piccolo, D. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Coal wash reject (CW) refers to the coarse fraction of a mining byproduct of longwall mining which typically comprises a well-graded cobble, gravel and sand mix. In the coal mining area of Wollongong, south of Sydney, Australia, there is a long history of reuse of CW as engineering fill, which is likely to continue with rising demand for sustainable practices. This paper summarises the properties of compacted CW from the Wollongong area as available in published literature. The paper then presents the results of bespoke oedometer tests and plate load tests completed by the authors to characterise the settlement behaviour of the CW in an engineered deep fill setting when the material is well compacted and subject to large overburden loads. The completed testing is used to assess the elastic Young’s modulus, long-term creep coefficient, and the collapse potential upon inundation of loosely compacted and well-compacted CW. Conclusions are drawn regarding the geotechnical suitability of CW as an engineered material in a mine or quarry rehabilitation setting.